Degree distribution optimization for LT codes and its application in link maintenance of cognitive radio - Benshun YI; Weiqing YAO (Tongxin xuebao)
The degree distribution has a great influence on the performance of Luby transform (LT) codes.Based on the link maintain model of cognitive radio system，the novel degree distribution of LT codes was obtained by using the THOA (two-layer hierarchical optimization algorithm) to combine the IPD (improved poisson distribution) which achieved high decoding success rate with low overhead and the robust soliton distribution (RSD) which achieved high decoding success rate with high overhead.Simulation results show that the proposed method with application to link maintenance in cognitive radio system can improve the reliability and efficiency of secondary communication.